EDUCAÇÃO AMBIENTAL CONTRA O TRÁFICO DE ANIMAIS SILVESTRES - Ferreira Lima, Edmar; da Costa Brito, Clecina; Jossany Almeida Brito, Mayra; Pereira de Oliveira, Rosivaldo; Cristhina Aragão Pereira, Cynara (Revista Form@re - Parfor/UFPI, 2026)
.